A simulation model of solid concrete beam containing Palm Oil Fuel Ash (POFA) and Expeneded Polystyrene (EPS) using finite element method - Rosli, Siti Nurhaliza; Osman, Mohamad Hairi; Mahyeddin, Mohd Eizzuddin (Elsevier, 2021)
First Concrete beam construction has contributed to a rise in the emission of carbon dioxide (CO2) gas, which is the key cause of global warming. To solve the effects, the materials for making concrete can be replaced by other environmentally friendly materials. In this case for concrete beam construction, Palm Oil Fuel Ash (POFA) and Expanded polystyrenes (EPS) would be used to substitute several percent of cement and aggregate. The use of POFA can produce high strength concrete and can also reduce waste disposal and EPS can produce lightweight concrete. This study is focusing on to analyse the silica structure of POFA by using X-Ray Diffraction (XRD) and to determine mechanical properties of concrete containing POFA and EPS by using ABAQUS software. For this project, the main factor why ABAQUS software was used as analytics software because the software is specifically designed to analyse advanced structural and heat transfer. For both very small and very large structures, it is designed for both linear and nonlinear pressure analyses. This ABAQUS software will help to compare between normal concrete and concrete containing POFA and EPS. The information contains the appropriate percentage of POFA and EPS in the solid concrete beam where performance in terms of displacement, stress and strain.